Improving Students’ Reading Comprehension by Using Herringbone Technique - Kautsara, Faza; Jaya, Wayan Satria; Herlisya, Destia (Lentera: Jurnal Ilmiah Kependidikan, 2022)
This research aimed to improve students’ reading comprehension by using Herringbone Technique. The subject of this research was the 10th IPS 1 of SMA YP Unila Bandar Lampung. It consisted of 34 students. This research used Classroom Action Research (CAR) which was consisted of 2 cycles. In collecting the data, the writer used test and non-test. The tests used in this research were formative and summative test. Meanwhile in non-test, the writer used observation sheet and field note. In analyzing the data, the writer used quantitative and qualitative method. Refers to the result of the test, it showed that there were 23 students who got score ≥70 with the percentage 64.67% in the first cycle. Meanwhile, there were 28 students who got score ≥70 with the percentage 82.35% in the second cycle. In the other hand, the mean score of the students’ learning activity in the first cycle was 6.84 and in the second cycle was 7.51. It showed that there was an increase in the students’ learning activity. Based on the result of the research, the Herringbone Technique can improve students’ reading comprehension in the tenth grade of SMA YP Unila.